(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Faces play an important role in human social interactions. An unaesthetic face can affect people’s physical, mental, psychosocial and emotional health, causing them to lose their confidence. Objective: Describe the current status of face perception on standardized images in students of Hanoi National University in 2023. Method: Cross-sectional descriptive study conducted on 259 students. Results: Short, straight male faces and straight, average female faces have the highest average scores of 8.25 and 8.61; Long, concave male and female face types have the lowest average scores of 2.09 and 2.52. Conclusion: Short, straight male faces and straight, average female faces are the most beautiful, concave, long male and female faces are the worst. There is no significant difference in the perception of beauty of facial types between student groups.